Blockchain Strategy Model in the Fisheries Supply Chain to Support the SDGs in the Fisheries Industry - Arie Wahyu Prananta; Indra Jaya Kusuma Wardana; I Wayan Suyadnya; Iqbal Mahcfud Fauzi (Postgraduate, University of Mataram, 2025)
Strategic implementation of blockchain in the fisheries industry can improve logistics efficiency and consumer confidence in ethically and sustainably sourced fishery products, which are important pillars for national and global food security. This strategic model essentially integrates blockchain technology into every stage of the fisheries supply chain to address issues such as lack of transparency, fraud, and unsustainable fishing. Its primary impact is the provision of reliable data on product origin, condition, and compliance with sustainability standards, thus directly helping the fishing industry contribute to the SDG targets. The performance of the fisheries industry supply chain is crucial to the success of food security and the achievement of the Sustainable Development Goals (SDGs). Key challenges in this sector include low transparency, distribution delays, IUU fishing practices, and unequal access to information among actors. Blockchain technology is considered capable of addressing these issues through a secure, transparent, and decentralized digital recording system. This study aims to design an optimal strategy for blockchain implementation in the fisheries supply chain based on an Operational Research (OR) approach, specifically using the goal programming method. Modeling results indicate that investment in a logistics traceability system and digitalization training for fishermen provide the greatest contribution to improving efficiency and food security. This study recommends cross-sector integration between the government, business actors, and blockchain technology providers.